The figure of pañji in Old Javanese sources; What is in a name? - Jákl, JiŘí (UI Scholars Hub, 2020)
Literary and epigraphic references to the figure of pañji in Old Javanese texts are analysed, and contextualized with much better-known references to the figure of Pañji in Middle Javanese texts. A hypothesis is offered that Old Javanese term pañji is best rendered as “court-name”. It is argued that young boys from elite families obtained their familiar court-name (pañji) at the very onset of their career at the court, where they served as pages and attendants of the royal family. They were also trained in arms, religious lore, and arts. Being since their childhood close to the king, they were trusted persons, and some of them made careers as high-ranking court officials, such as Dəmuṅ or Kanuruhan. Others, denoted ācārya, were trained as “masters of divine weapons”, Tantric ritual specialists, who were in charge of the so-called “divine weaponry“ (diwyāstra), mantra- infused ordinary weapons, an arsenal well-known in Old and Middle Javanese texts. Vestiges of this ritual lore have survived in Java until modern times.